Hearing Children’s Perceptions and Attitudes towards Irish Sign Language (ISL) and the Deaf Community - Mc Cann, Deirdre (Marino Institute of Education, 2020)
Irish Sign Language (ISL) was recognised as an official language of Ireland in 2017. The Deaf community spent over 30 years campaigning for this recognition. Irish and English are the two other national languages of Ireland, which are taught in the new primary language curriculum (PLC) that was introduced to all primary schools in 2019. ISL is referred to in the new PLC, as it aims to promote language awareness. This study investigates the perceptions and attitudes of hearing children towards ISL and the Deaf community. Quantitative and qualitative data was gathered through the distribution of anonymous questionnaires. The sample group comprised 32 pupils from 3rd to 6th classes in a mainstream primary school in Dublin, Ireland. The children had some prior knowledge of basic ISL and Deaf culture. The findings reflected an overall positive perception of, and attitude towards both ISL and the Deaf community. The majority of children perceived ISL as a legitimate language, and recognised that it was a language used by the Deaf community. Based on these findings, along with those from previous studies it is postulated that the concurrent learning of Deaf culture alongside ISL contributes to more positive perceptions and attitudes. These findings have implications for teachers and policy makers for any possible future efforts to include ISL in the primary school curriculum. For example, by incorporating an element of Deaf Studies into the primary teacher education curriculum to raise awareness in schools of ISL and the Irish Deaf community.
Keywords: Research Subject Categories